Lime, inoculum, and phosphorous input supplementation under rain-fed soybean in Ghana's northern savannas - Awuni, George A.; Reynolds, Daniel B.; Dodds, Darrin; Denwar, Nicholas N.; Abdulai, Alhassan L.; Asungre, Peter A.; Yahaya, Iddrisu; Goldsmith, Peter D. (Frontiers in Sustainable Food Systems, 2023)
Introduction Recent prices in soybean have spurred interest in motivating growers into input integration to improve yields across the northern savannas of Ghana. This requires more knowledge of input integration to increase soybean yield and profitability across production areas. Materials and method A 3-yr study was conducted in three locations at Manga, Nyankpala, and Wa in Ghana's northern savanna to identify the best-yielding input combination under a rain-fed environment. The experiment used “Jenguma” soybean cultivar with lime, inoculum, and phosphorus in a 2 × 2 × 2 factorial arrangement with four replications. Eight treatment combinations (control included) were used to assess soybean yield, yield components, rain use efficiency, and economic profitability. The single-input application of lime (T1), inoculum (T2), and phosphorus (T4) was the low-input, lime × inoculum (T3), lime × phosphorus (T5), and (inoculum × phosphorus) (T6) as medium input, T7 (lime × inoculum × phosphorus) was high input, and a no-input treatment (control). Results The soils were inherently low in fertility, and weather variability during the reproductive stages was a significant limiting factor to improving grain yield across locations. Grain yield was highest in 2017 at Manga and Nyankpala, but in 2019 at Wa. Except at Manga, grain yield and rain use efficiency (RUE) were highest in the high input system (T7). However, marginal net benefits (MNB) and marginal rate of returns (MRR) were highest in the low input system (T2) across locations. The low (T1) and medium (T3) input systems (except Nyankpala) were dominant for MNB and MRR due to the high cost of the lime product. Discussion These results suggest that smallholder farmers prefer low input (T2) with the least cost of production and the highest marginal net benefit and marginal rate of returns. Nevertheless, producers would have to evaluate their resource base and the cost of nutrient integration for sustainability. Conclusion This paper recommends further studies on lime rates to determine profitability, lime's long-term (residual) effect, and the synergic impact of inoculum and phosphorus.